2022
DOI: 10.3390/coatings12050651
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manufacturging Parameters on Microstructure, Chemical Composition, Microhardness, Corrosion and Wear Resistance of ZrC Coatings Produced on Monel®400 Using Laser Processing Technology

Abstract: This paper presents the influence of production parameters and analysis of ZrC coatings production on Monel®400 substrate. The effects of laser beam power on the microstructure, chemical composition, corrosion resistance and on selected mechanical properties such as microhardness and wear resistance were investigated. The investigation consisted of the production of composite coatings using laser processing of pre-coatings made in paste form on a nickel based alloy (Monel®400). In the studies, a diode laser wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Bartkowska et al [6] reported that a diffusion-borided layer of Monel ® alloy 400 processed by diode laser had better corrosion resistance, hardness, and wear resistance properties than the substrate material. Bartkowski et al [10] reported that there is a possibility to deposit ZrC composite coatings on a Ni-Cu alloy through laser melting.…”
Section: Introductionmentioning
confidence: 99%
“…Bartkowska et al [6] reported that a diffusion-borided layer of Monel ® alloy 400 processed by diode laser had better corrosion resistance, hardness, and wear resistance properties than the substrate material. Bartkowski et al [10] reported that there is a possibility to deposit ZrC composite coatings on a Ni-Cu alloy through laser melting.…”
Section: Introductionmentioning
confidence: 99%